A thermodynamic model for feldspars in KAlSi3O8−NaAlSi3O8−CaAl2Si2O8 for mineral equilibrium calculations. (18th November 2021) - Holland, Tim J. B; Green, Eleanor C. R; Powell, Roger
Abstract: Activity–composition ( a ‐ x ) relations for feldspars for petrological calculations in KAlSi3 O8 −NaAlSi3 O8 −CaAl2 Si2 O8 are calibrated using literature data for (i) plagioclase cation exchange experiments at 600 and 700°C, (ii) experimental ternary feldspar pairs at 880 − 900°C, (iii) the alkali feldspar solvus, and (iv) the dry melting loop for plagioclase. The results are tested against the calorimetric heat of solution data and the experimental pressures for plagioclase coexisting with grossular, wollastonite, and quartz. As the aim is to produce a ‐ x relations suitable for petrological modelling, we do not attempt to model complex structural phenomena in feldspar, except where they appear to contribute significantly to the energetics of high‐temperature mixing. Seven models were investigated, using various formulations of entropy of mixing together with the van Laar model for non‐ideal mixing. The model (4TR) that most satisfactorily reproduces the experimental data is one in which Al and Si partially order onto the four tetrahedral sites, approximated by reducing the tetrahedral site entropy of mixing by a factor of 4. When combined with an ordered albite, this model allows a peristerite gap closing at 600°C at the albite composition. The resulting activity‐composition relations for feldspar should be applicable in petrological phase equilibrium calculations over a large range of geologically relevant pressure and temperature.